A comparison between the lichen flora of coastal and inland areas in the Julianehåb District, South Greenland. - Steen Hansen, Eric (Meddelelser om Grønland, 1978)
In 1969 a total of 1200 collections of 201 species of macro- and microlichens were made in eight localities in the Julianehåb District in South West Greenland. Four of the species, viz. Caloplaca Flavovirescens (WULF.) DALLA TORRE & SARNTH., Candelariella coralliza (NYL.) MAGN., Lecidea symmicta (ACH.) ACH. and Rhizocarpon eupetraeum (NYL.) ARN., are new additions to the lichen flora of Greenland. These species as well as other lichens of particular interest are discussed separately. The distribution and occurrence of the species is outlined. In regard to the number of species there is a clear difference between localities far off the coast and localities near the coast: The former regions have a much richer lichen flora than the latter. Climatic and geological conditions are of great importance for the distribution of a large number of the lichen species. The distribution of four species are mapped.